2013
DOI: 10.1002/j.1532-2149.2013.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical nerve stimulation and conditioned pain modulation influence the perception of pain in humans

Abstract: Background Research in animal models suggest that transcutaneous electrical nerve stimulation (TENS) and conditioned pain modulation (CPM) produce analgesia via two different supraspinal pathways. No known studies have examined whether TENS and CPM applied simultaneously in human subjects will enhance the analgesic effect of either treatment alone. The purpose of the current study was to investigate whether the simultaneous application of TENS and CPM will enhance the analgesic effect of that produced by eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 51 publications
(82 reference statements)
3
20
0
2
Order By: Relevance
“…These studies suggest that TENS is more effective for mechanical deep tissue pain than thermal cutaneous pain. In healthy controls we and others routinely show that TENS reduces PPTs [45,48,51]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies suggest that TENS is more effective for mechanical deep tissue pain than thermal cutaneous pain. In healthy controls we and others routinely show that TENS reduces PPTs [45,48,51]. …”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the reduced effect over time is due to the development of tolerance to the TENS stimulation. Studies that have evaluated the effect of repeated TENS use have demonstrated tolerance to TENS after five days of repeated application when given at the same dose (frequency and intensity) in healthy human subjects and in animal studies [10,45]. Factors that prolong this tolerance include alternating between low and high frequency [23] and increasing the amplitude over time [62].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of pain inhibition during a CPM test was obtained from previous data on CPM and PPT in healthy controls by our research team (Correa et al 2013; Liebano et al 2013). At a significance level of 0.05 and power of 95 %, it was calculated that a minimum of 21 participants was required in each group (Minitab, v. 15, State College, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Some cells in the VPL in thalamus are known to respond selectively to pinch stimuli [20, 32], at least under anesthesia, implying that labeled lines might account for some behavioral responses to nociceptive input. However, there are other cells in the spinal dorsal horn, the wide dynamic range cells [46],that receive excitatory input from both nociceptive and non-nociceptive sensory inputs.…”
Section: Introductionmentioning
confidence: 99%